Availability and Usage of Library School Resources as Predictors of Reading Habits among Secondary School Students in Oredo Local Government, Edo State, Nigeria - Oluwatosin , Adedoyin; Akporhonor, Blessing Amina (Record and Library Journal, 2021)
Background of the study: It is the responsibility of every school library to promote and support the National Policy of Education by providing equitable school library resources. Purpose: This study investigates the availability and usage of school library resources as predictors of reading habits among secondary school students in Oredo Local Government (LG) of Edo state, Nigeria. Method: Descriptive survey design was adopted for the study. The population comprises of 362 students in Senior Secondary Students III (SSS3) in two public and two private senior secondary schools in Oredo LG, Edo state, Nigeria. Stratified random technique was used to select the four schools and 200 copies of questionnaires were administered to the respondents of which only a total of 190 copies of questionnaire were returned which represents 95% return rate. Findings: Findings revealed that most of the sampled schools have library resources; however most of the resources were obsolete. Results show that most of the respondents do not make use of the resources regularly and that the respondents are majorly interested in text related to their subject in school. It was discovered that none of the schools have a trained librarian working in their libraries. Conclusion: The study established that availability and usage of library resources cannot effectively predict the reading habit of secondary school students in Oredo LG, Benin-City.